Circular Economy Approach for Sustainable Tree Litters Waste Management, study case in Universitas Diponegoro - Ariyanti, Dessy; Ambariyanto, Ambariyanto; Utama, Yos Johan; Sugianto, Denny Nugroho; Hapsari, Farida Diyah (Universitas Diponegoro, 2024)
Universitas Diponegoro, with an open forest area and planted vegetation of 30 – 40%, produced vast amounts of organic waste, especially tree litter. Piles of tree litter are everywhere if it is not properly managed. Universitas Diponegoro has taken a comprehensive approach to handling leaf and tree litter by converting it into economically valuable and beneficial products to meet the objectives of SDGs 12, which are focused on Responsible Consumption and Production. Through the Technical Implementation Unit for Occupational Safety, Health, and Environment (UPT K3L) Universitas Diponegoro has pyrolyzed tree branches to create liquid smoke and anaerobically converted leaf waste into compost. Later, the liquid smoke produced by pyrolysis and compost can achieve the consumer demand standard. In addition, from the policy approach, it is mandatory for every building to handle tree litter surrounds into compost using composting pits and composting bags. The circular economy idea has been incorporated into waste management at Universitas Diponegoro.